Research and Test of the Effect of Tooth Surface Friction on Dynamics Characteristic of Double Circular Arc Gear - Liu Xiaojie; Zhang Ruiliang; Zhang Zhiyu (Jixie chuandong)
Because of the particularity of the design of double circular arc gears, the influence of tooth surface friction on the transmission of double circular arc gears is often neglected in the past research on the dynamic characteristics of double circular arc gears. The precise model of double circular arc gear is designed by parameterization, and the dynamics performance of double circular arc gear is simulated by Adams software combined with multi-body dynamics analysis theory. By setting different friction coefficients between tooth surfaces, the influence of tooth surface friction on the dynamic performance of double circular arc gear transmission is analyzed, which is further verified by the transmission test of double circular arc gear. The simulation results provide some reference for the correlation between the double circular arc gear transmission and the tooth surface friction.